Spiritual Health and Coping Strategies Among Medical Students in Crisis Situation: A Cross-Sectional Survey - Naveed Mansoori (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective: To assess the spiritual health of medical students and  to  identify  the  coping  strategies used in crisis situation. Methods: A cross sectional study was done during 2017 at  Hamdard  College  of  Medicine  &  Den- tistry, Karachi. Simple random sampling technique was used for data collection. Spiritual Health As- sessment Scale was  used to  measure the  level of  spiritual health and  Brief COPE scale was  used      to assess the varying coping strategies practiced in response  to  stress.  Descriptive  analysis  was  done, overall spiritual health  score  was  obtained,  while  frequencies  of  various  coping  attributes were determined by using SPSS version 22. Independent t-test was used for association of different domains of spiritual health between male and female students. P-value <0.05 was considered as statistically significant. Results: Out of total  511  students, 298  (58.3%) were male and  213  (41.7%) female.  Mean age  was  21 ± 1.8 years. Students 261 (51.1%) were found  to  have  good  spiritual  health.  Statistically  signifi- cant (P<0.05) differences was observed between male and female students doing gratitude, act ac- cording to moral  values,  introspection,  knowing  purpose  of  own  life,  own  strengths,  solutions  to deal with weaknesses, performing yoga to achieve and maintenance  of  spirituality.  Students  using active coping were 146 (28.6%), substance use 289 (56.6%), turning to religion 188 (36.8%) and humour 178 (34.4%). Conclusion: The study reveals that most of the medical students have good spiritual health. Coping strategies used by medical students during  their  academics  are  mainly  substance  use,  active  cop- ing and turning to religion for management of stress.